Yapıştırma Akrilik Yavaş Üst Çene Genişletmesinin Dental Ark Ve Ark Perimetresine Etkisi - Sevil Akkaya; Sumru Hızlan Lorenzon (Galenos Yayinevi, 1997)
"Dental arch and arch perimeter changes concurred with bonded slow maxillary expansion". This study-was carried out in order to evaluate dental arch, and arch, perimeter changes with bonded minne-expander appliances. 12 patients having maxillary bilateral cross-bites caused by basal apical narrowness, concurrently showing a Angle Class I or a Class II molar relationship were selected. Orthodontic casts and hand-wrist radiographs which were taken at the beginning of treatment, at the end of treatment and at the end of retention period of these patients formed the material of the research. The treatment time varied from 2.00-5.16 months. At the end of active treatment same appliances were worn for retentive purposes for an additional 3 months. Throughout the research period; increases in the transversal width between the upper first molars, upper first premolars, upper canines, lower first molars, lower canines and in the upper arch perimeter were obtained.